HUBUNGAN PENGETAHUAN DAN SIKAP IBU DALAM PEMBERIAN MP-ASI TERHADAP KERAGAMAN PANGAN ANAK USIA 6–24 BULAN DI KELURAHAN TANJUNG PINANG - Chendy Yugu Tanca; Silvia Mawarti Perdana; Ashar Nuzulul Putra; Puspita Sari (STKIP Subang, 2026)
Background: Dietary diversity is an important indicator of food consumption quality among children aged 6–24 months and is assessed using the Minimum Dietary Diversity (MDD) indicator. Maternal knowledge and attitudes regarding complementary feeding may influence children's dietary diversity. This study aimed to determine the relationship between maternal knowledge and attitudes regarding complementary feeding and dietary diversity among children aged 6–24 months in Tanjung Pinang Village, East Jambi District, Jambi City. Methods: This study used a quantitative cross-sectional design. A total of 60 mothers with children aged 6–24 months were selected using purposive sampling. Data were collected using questionnaires and a 24-hour food recall form. Data were analyzed using the Chi-Square test and Odds Ratio (OR). Results: A total of 44 respondents (73.3%) had good knowledge, 42 respondents (70.0%) had positive attitudes, and 44 children (73.3%) achieved MDD. There was a significant relationship between maternal knowledge and dietary diversity (p=0.000; OR=30.00). However, no significant relationship was found between maternal attitudes and dietary diversity (p=0.252; OR=0.446). Conclusion: Maternal knowledge was significantly associated with dietary diversity among children aged 6–24 months, whereas maternal attitudes were not significantly associated with dietary diversity.